2022
DOI: 10.1039/d2ra01397e
|View full text |Cite
|
Sign up to set email alerts
|

Quinolizinium-based fluorescent probes for formaldehyde detection in aqueous solution, serum, and test strip via 2-aza-Cope rearrangement

Abstract: Novel quinolizinium-based fluorescent probes were designed based on 2-aza-Cope rearrangement reaction to detect formaldehyde in aqueous solution, serum, and paper format. The use of a geminal dimethyl group allows fast response within 15 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The mechanism proceeds through an intermediate chairlike structure. The rearrangement shifts single and double bonds between two allylic parts . In this case, sigmatropic rearrangements are involved in pericyclic reactions, where the σ bond in the adjacency of pi systems is transferred and the overall pi system reestablishes itself (Figure ).…”
Section: Organic Chemosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism proceeds through an intermediate chairlike structure. The rearrangement shifts single and double bonds between two allylic parts . In this case, sigmatropic rearrangements are involved in pericyclic reactions, where the σ bond in the adjacency of pi systems is transferred and the overall pi system reestablishes itself (Figure ).…”
Section: Organic Chemosensorsmentioning
confidence: 99%
“…The rearrangement shifts single and double bonds between two allylic parts. 25 In this case, sigmatropic rearrangements are involved in pericyclic reactions, where the σ bond in the adjacency of pi systems is transferred and the overall pi system reestablishes itself ( Figure 3 ). The total number of sigma and pi bonds is preserved in the end.…”
Section: Organic Chemosensorsmentioning
confidence: 99%
“…Though governments explicitly prohibit the addition of excessive amounts of FA to household products, it is still detected in cosmetic products, fruit transportation, fish preservation, etc for preventing spoilage due to the ability to effectively inhibit the survival of most bacteria and fungi in water [4][5][6]. For efficient and simple field detection, electrochemical sensors have been utilized for FA detection instead of spectrophotometry, high-performance liquid chromatography, gas chromatography, fluorometric methods, polarography, etc [7][8][9][10][11][12]. Finding an efficient electrode material for an electrochemical sensor, so that it has a fast response performance to FA, is the key to the current breakthrough in FA electrochemical detection technology [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…[11d,12n,13-16] It has been also recently shown that compounds possessing the quinolizinium moiety with extended π-conjugated systems can be prepared on Au surface from the parental pyridinium salt via cyclodehydrogenation reactions. [17] As far as potential application of compounds with the quinolizinium moiety is concerned, they have so far found application as DNA intercalators, [18] photosensitizers in biological systems, [19] photosensitizers in biological systems, [13,14] probes for detection of small molecules, [20] photocatalysts, [21] or non-linear optical chromophores. [22] One class of the above-mentioned Ne-PAHs are N-embedded pyrene derivatives (Figure 1), i. e. azapyrenes that could be considered as suitable and interesting model substances or intermediates en route to NeNs.…”
Section: Introductionmentioning
confidence: 99%
“…As far as potential application of compounds with the quinolizinium moiety is concerned, they have so far found application as DNA intercalators, [18] photosensitizers in biological systems, [19] photosensitizers in biological systems, [13,14] probes for detection of small molecules, [20] photocatalysts, [21] or non‐linear optical chromophores [22] …”
Section: Introductionmentioning
confidence: 99%